2021
DOI: 10.1175/jhm-d-20-0164.1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of the Performance of Spatial Interpolation Methods for Rainfall Estimation Using Commercial Microwave Links

Abstract: Using signal level measurements from commercial microwave links (CMLs) has proven to be a valuable tool for near-ground 2-D rain mapping. Such mapping is commonly based on spatial interpolation methods, where each CML is considered as a point measurement instrument located at its center. The validity of the resulted maps is tested against radar observations. However, since radar has limitations, accuracy of CML-based reconstructed rain maps remains unclear. Here we provide a quantitative comparison of the perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Here, the differences between the two cases were noticeable, but they were less significant than for the simplified Gaussian-shaped rain cells. In Eshel et al (2021), however, the Kriging technique (spatial covariance-based interpolation) was also applied, showing similar results. A potential point of failure in GMZ as implemented in Eshel et al (2021) was suggested for specific scenarios, where the redistribution of rain intensities between the VRGs on a given CML is more detrimental than assuming a single point in the center.…”
Section: D Near-ground Rain Retrieval-practical Considerationsmentioning
confidence: 78%
See 2 more Smart Citations
“…Here, the differences between the two cases were noticeable, but they were less significant than for the simplified Gaussian-shaped rain cells. In Eshel et al (2021), however, the Kriging technique (spatial covariance-based interpolation) was also applied, showing similar results. A potential point of failure in GMZ as implemented in Eshel et al (2021) was suggested for specific scenarios, where the redistribution of rain intensities between the VRGs on a given CML is more detrimental than assuming a single point in the center.…”
Section: D Near-ground Rain Retrieval-practical Considerationsmentioning
confidence: 78%
“…A similar approach was used on real rainfall patterns, obtained from a radar product of the German Weather Service, for different aggregation intervals (Eshel et al, 2021), where the attenuation of an actual 808-CML network was simulated (referred to as a "semi-real" study). Here, the differences between the two cases were noticeable, but they were less significant than for the simplified Gaussian-shaped rain cells.…”
Section: D Near-ground Rain Retrieval-practical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, OK has its own limitations and needs to make some assumptions, such as isotropy and statistical stationarity. Eshel et al [71] compared the performance of the IDW and OK algorithms, and the results show that the performance improves with the increase in decorrelation distance (i.e., less intermittent field). The OK interpolation technique uses more prior/auxiliary information and correlates slightly better with ground truth than IDW, and the performance of OK and IDW-based algorithms with multiple points representing a CML is slightly better than that with only one point representing a CML.…”
Section: Rainfall Map Reconstructionmentioning
confidence: 99%
“…In the past, various methodologies have been tested and applied for spatial interpolation of CML retrieved rainfall measurements, considering different spatial scales (e.g., Fencl et al, 2013;Overeem et al, 2013;D'Amico et al, 2016;Haese et al, 2017;Chwala and Kunstmann, 2019;Graf et al, 2020;Eshel et al, 2021). Here, we exploited the simple and robust IDW method (Shepard, 1968) for both RG and CML measurements.…”
Section: Spatial Interpolation Of Rainfall Datamentioning
confidence: 99%